(untitled) (Texas Journal of Philology, Culture and History, 2023)
Medical terminology serves as the foundation of effective communication within the healthcare field. Proficiency in medical terminology is essential for healthcare professionals to accurately describe symptoms, conditions, procedures, and medications. However, learning medical terminology can be challenging due to the vast number of complex terms. This article explores innovative methods of teaching medical terminology that promote active learning, engage students, and enhance retention.